Mikropropagasi Anggrek Phalaenopsis dengan Menggunakan Eksplan Tangkai Bunga - YUSWANTI, HESTIN; DHARMA, I PUTU; UTAMI, UTAMI; WIRAATMAJA, I WAYAN (Agrotrop : Journal on Agriculture Science, 2015)
Micropropagation of Phalaenopsis Orchid Using Explants of Flower Stalk. This studyaimed to obtain optimum media formulations for bud multiplication of micropropagation ofPhalaenopsis orchid using flower stalk. This study employed Completely Randomized Designwith 5 different treatments, i.e. M0 = MS + 150 ml/l coconut water + 2 g activated charcoal,M1 = MS + 1 ppm IBA+ 1 ppm BAP + 150 ml/l coconut water + 2 g/l activated charcoal M2= MS + 1ppm IBA+ 2 ppm BAP+ 150 ml/l coconut water + 2 g/l activated charcoal, M3 =MS + 1 ppm IBA+ 3 ppm BAP + 150 ml/l coconut water + 2 g/l activated charcoal, M4 = MS+ 1 ppm IBA+ 4 ppm BAP + 15 0ml/l coconut water + 2 g/l activated charcoal. Eachtreatment consists of 5 replicates, so there were 25 units experiment, with 3 explants each.Results of this study revealed that M2 media exhibited the best growth, as shown by swellingbuds (23.77 Days After Planting/DAP), earliest buds formation (49.33 DAP) and height ofbuds of 2,12cm.
Keywords: Flower Stalk; Phalaenopsis orchid; micropropagation; IBA and BAP